2015
DOI: 10.1016/j.brq.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Investment decisions of companies in financial distress

Abstract: This paper analyzes the influence of financial distress on the investment behavior of companies. The analysis includes companies from Germany, Canada, Spain, France, Italy, UK and USA, which cover a wide spectrum of different institutional environments. The methodology used is panel data estimation using the Generalized Method of Moments (System-GMM), thereby allowing control of both unobservable heterogeneity and the problems of endogeneity in explanatory variables. The results show that the influence of fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 39 publications
0
38
0
4
Order By: Relevance
“…Using the generalized method of moments (GMM) system, from panel data, the results showed that the influence of financial distress on investment is distinct according to the investment opportunities available to companies. So, companies in difficulties with fewer opportunities have the highest propensity to underinvest, while firms in problems with better opportunities do not present different investment behaviour than healthy companies (López-Gutiérrez et al 2015).…”
Section: Earnings Management and Bankruptcy Predictionmentioning
confidence: 98%
“…Using the generalized method of moments (GMM) system, from panel data, the results showed that the influence of financial distress on investment is distinct according to the investment opportunities available to companies. So, companies in difficulties with fewer opportunities have the highest propensity to underinvest, while firms in problems with better opportunities do not present different investment behaviour than healthy companies (López-Gutiérrez et al 2015).…”
Section: Earnings Management and Bankruptcy Predictionmentioning
confidence: 98%
“…The System GMM methodology has been commonly used to control endogeneity problems (e.g. Beck et al, 2000; López-Gutiérrez et al, 2015; Uotila et al, 2009) and seems to be superior to the other option to control the endogeneity using panel data: Diff GMM. Finally, according to Heid et al (2012), System GMM is more adequate when data show high persistence as it is in our case.…”
Section: Research Design and Samplementioning
confidence: 99%
“…In a recent study, Khanam (2017) also reported the influence of demographic factors such as age, level of education, occupation, trading experience, and level of investor income. In contrast, behavioral finance researchers argue that investors tend to behave irrationally in the investment decision-making process due to the influence of several psychological factors (Kiyilar & Acar, 2013;López-Gutiérrez et al, 2015;Chen et al, 1995).…”
mentioning
confidence: 99%